2022
DOI: 10.1021/acs.jpca.2c04873
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopy of Retinoic Acid at the Air–Water Interface

Abstract: The spectroscopy of all-trans-retinoic acid (ATRA), an important molecule of biological origin that can be found in nature, is investigated at the air–water interface using UV–Vis and IR reflection spectroscopy. We employ a UV–Vis reflection absorption spectroscopy (RAS) experiment along with infrared reflection absorption spectroscopy (IR-RAS) to probe ATRA at the air–water interface. We elucidate the factors influencing the spectroscopy of ATRA at the air–water interface and compare its spectra at the water … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 91 publications
0
4
0
1
Order By: Relevance
“…IR reflection–absorption spectra of α-keto acids at the air–water interface were obtained using a home-built IR-RAS setup and methodology as described previously. ,, Briefly, a PTFE trough from KSV-NIMA (14.5 cm × 7 cm × 0.5 cm) was optionally equipped with a Wilhelmy microbalance and Delrin barriers. The microbalance and barriers were used when studying insoluble molecules and were removed when studying soluble molecules.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…IR reflection–absorption spectra of α-keto acids at the air–water interface were obtained using a home-built IR-RAS setup and methodology as described previously. ,, Briefly, a PTFE trough from KSV-NIMA (14.5 cm × 7 cm × 0.5 cm) was optionally equipped with a Wilhelmy microbalance and Delrin barriers. The microbalance and barriers were used when studying insoluble molecules and were removed when studying soluble molecules.…”
Section: Methodsmentioning
confidence: 99%
“…Air–water interfaces are ubiquitous in natural environments, both on the surface of oceans and on atmospheric aerosols. Recent studies have shown that the unique properties of these interfaces lead to morphological and chemical changes that are not fully understood. These interfaces concentrate and align organic material, and even small, soluble organic molecules partition preferentially to the water surface. , The resulting organic films at aqueous interfaces can control molecular transfer between the vapor and condensed phases, altering their optical properties and thereby affecting the earth’s radiative balance and other atmospheric processes. , Recent reports in the literature have repeatedly demonstrated enhanced reactivity and increased reaction rates in confined microenvironments (e.g., microdroplets, nanoemulsions, and aerosol), , highlighting the critical question of the role that the interface may play in these observed effects. In order to better understand how such aqueous interfaces may provide auspicious reaction environments, fundamental studies that explore the detailed surface behavior of model systems of organics are needed.…”
Section: Introductionmentioning
confidence: 99%
“…飞秒时间分辨数据准确揭示了苯酚 的光电离反应在界面的速度是本体水相的10 4 倍. de Al-wis等人 [29] 提出了一种偏振调制红外反射吸收光谱(polarized modulated-infrared reflection-absorption spectroscopy, PM-IRRAS), 用于在气/液/固界面原位观 察分子吸附行为. Rana等人 [49] 联合时间分辨干涉法和 区(右)) [31] . (b)…”
Section: 线性光谱和非线性光谱在近些年的研究中得到了unclassified
“…Figure 5 (Color online) Spectral methods for dynamic surfaces/interfaces. (a) P-polarized IR-RAS spectra (930 to 1800 cm −1 region (left) and 2000 to 3050 cm−1 region (right)) of ATRA-SA-d 35 at the interface[31] …”
mentioning
confidence: 99%
“…Numerous processes in chemistry and biology are driven by the interactions of charged species with interfaces. Developing a fundamental, molecular-level understanding of the forces that govern interactions and localization of specific chemical species to complex interfaces is critical to understanding these processes. In particular, liquid–liquid interfaces and multicomponent surfactant compositions can produce highly heterogeneous interfaces whose local environments vary significantly. , Controlling the surfactant composition, the bulk supporting liquid composition, or the temperature allows for a highly tunable system that can be tailored to specific applications. However, determining the fundamental link between molecular properties and bulk behavior has been a largely empirical endeavor, and developing general theories that provide a semiquantitative prediction of interfacial composition has remained challenging . Reverse micelles (RMs) offer an ideal model system to understand the effects of charged interfaces on encapsulated species and the water structure of the aqueous interior. RMs are thermodynamically stable water-in-oil emulsions with surfactant composition, bulk phase properties, and overall vesicle size that can be precisely controlled. The wide range of variables that can be modified in RMs create a challenge for arriving at a molecular description of observed phenomena across various chemical applications. …”
Section: Introductionmentioning
confidence: 99%